(untitled) - Nord, Erik (New York, 1999)
This book is a comprehensive and fully up-to-date account of what it means to try to quantify health in distributing resources for health care. It offers an elegant new approach to comparing the costs and benefits of medical interventions. Erik Nord questions Cost-Utility Analysis (CUA) and the feasibility of measuring patients' quality of life meaningfully in numerical terms. He presents an alternative approach called cost-value analysis in which representative samples of the general public express preferences among different health-care programs
Keywords: Health care rationing,Medical care,Quality of life,Chăm sóc y tế,Chất lượng sống; Cost effectiveness,Mathematical models